Digital Personnel Systems: Navigating 21st Century Office Management Learning in Vocational Schools - Tri Nugroho Budi Santoso; Lelahester Rina; Destri Sambara Sitorus (Dinamika Pendidikan, 2025)
Competency in Office Management and Business Services at Vocational Schools (SMK) in Indonesia faces the challenge of preparing skilled human resources for the digital age. Currently, learning remains suboptimal due to limited technological facilities and a curriculum that is not fully aligned with industry needs. Consequently, relevant digital learning media are required to improve students' competencies in line with 21st-century demands, integrating technology, automation, and connectivity. This research aimed to develop and test the feasibility of the Digital Human Resources System (SIKEDIG) as a learning tool for the Office Management and Business Services specialization.  The study employed a Research and Development (R&D) approach using the ADDIE model. Feasibility testing involved six experts and practitioners and used a 5-point Likert scale. The results indicated that SIKEDIG was rated as "Highly Feasible" by language experts (mean score 4.5) and practitioners (mean score 4.5), while information systems experts rated it as "Feasible" (mean score 4.2). Based on evaluation and feedback, SIKEDIG was enhanced with new dashboard features, including attendance and employee recruitment trends. In conclusion, this research successfully developed and validated SIKEDIG as a feasible digital learning tool for vocational office administration programs.